HUBUNGAN ANTARA POLA ASUH PERMISIF DENGAN MOTIVASI BELAJAR REMAJA DI SMP YAYASAN MARDI LESTARI MEDAN - Indo Mora Siregar; Dwi Nursiti; Delimawati Hutauruk (JURNAL PSYCHOMUTIARA, 2022)
This study aims to determine the relationship of the origin pattern : permissive with youth learning motivation at the SMP Lestari Medan Gatot Subroto Fondalition SNIP The setting that became the target og this writing was because the author saw many teenagers at Yayaan Maari Middle Scholl who had low learning motivation. This happnes because student have a strong punuhisit pattern such as parents who do not know how to learn about children‟s learning at scholl, anda teach their children who they are so that the parenting style is not fulfilled The subject of this students at Mardi Lestari Foundation Junior High School Medan as many students as many as 52 people this subject is students Mletode this method uses data collection in this study using the technique and sampling technique in the research using a smple of fingers where mpel does not meet from  100 or starts 100 the results of this plot represent babu ola znih permissive is the category lingp „‟as hingh as (82,62%) or 44 people, and motivation to study in category high amounting to (64,46%) or 33 people grade score you negatife.